2016
DOI: 10.2463/mrms.mp.2015-0083
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese, Multicenter, Open-label, Phase 3 Study to Investigate the Safety and Efficacy of Gadobutrol for Contrast-enhanced MR Imaging of the Central Nervous System

Abstract: Purpose:Gadobutrol 1.0 M is macrocyclic gadolinium-based contrast agent for magnetic resonance imaging (MRI). This multicenter, open-label, phase 3 study aimed to investigate the efficacy and safety of gadobutrol-enhanced versus unenhanced MRI in the visualization and diagnosis of central nervous system (CNS) lesions in Japanese patients.Methods:A total of 223 patients referred for contrast-enhanced MRI of the CNS underwent unenhanced and gadobutrol-enhanced (0.1 mmol/kg body weight) MRI. The unenhanced and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Pivotal phase 3 [ 20 24 ] and 4 [ 25 , 26 ] trials have firmly established the diagnostic efficacy of gadobutrol in adult patients undergoing diagnostic CE MRI of brain lesions (Table 2 ), including for diagnosing primary and metastatic brain tumours. With the exception of the REMIND trial in patients with primary brain tumours [ 25 ] and a phase 3 trial in patients with known or suspected brain metastases [ 24 ], all other trials included patients with primary or metastatic brain tumours [ 20 23 , 26 ] and, in some instances, also included patients with non-tumour brain lesions (e.g. white matter disease, vascular lesions, infarct, haemorrhage, infective/inflammatory disease) [ 20 , 21 , 26 ].…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 99%
See 2 more Smart Citations
“…Pivotal phase 3 [ 20 24 ] and 4 [ 25 , 26 ] trials have firmly established the diagnostic efficacy of gadobutrol in adult patients undergoing diagnostic CE MRI of brain lesions (Table 2 ), including for diagnosing primary and metastatic brain tumours. With the exception of the REMIND trial in patients with primary brain tumours [ 25 ] and a phase 3 trial in patients with known or suspected brain metastases [ 24 ], all other trials included patients with primary or metastatic brain tumours [ 20 23 , 26 ] and, in some instances, also included patients with non-tumour brain lesions (e.g. white matter disease, vascular lesions, infarct, haemorrhage, infective/inflammatory disease) [ 20 , 21 , 26 ].…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 99%
“…of detected lesions/pt 2.97 vs. 2.65 (NI) c ; LCE 2.86 vs. 0.93*** (SUP) c ; LBD 2.94 vs. 1.92*** (SUP) c ; LIM 2.35 vs. 1.57*** (SUP) c Katakami et al [ 24 ] (151) GAD 0.1 and 0.2 vs. GAT 0.2 Overall % rated as good or excellent: LCE ≥ 86 and ≥ 90 vs. ≥ 87; LBD ≥ 67 and ≥ 74 vs. ≥ 71 No. of detected lesions/pt c 6.28 and 6.92 vs. 6.87 (NI) Tanaka et al [ 23 ] (221) GAD 0.1 d vs. UMRI No. of detected lesions/pt 11.09 vs. 10.79 (NI) c LCE 2.87 vs. 0.95*** (SUP) c ; LBD 3.20 vs. 2.14*** c ; LIM 2.28 vs. 1.15*** (SUP) c Phase 4 trials REMIND [ 25 ] (234) GAD 0.1 vs. GAD-ME 0.1 % rated as good or excellent for overall lesion visualization and characterization (range across readers): 93.2–99.6 vs. 90.6–100% c (NI) LSM BGD (range across readers): SNR − 10.3 to − 14.6 e ; CNR − 7.4 to − 23.6 e ; % LCE − 13.2 to − 15.7 e Generally, readers had no specific preference for GAD vs. GAD-ME for LBD, LIM, LCE; no difference for diagnostic confidence TRUTH [ 26 ] (209) GAD 0.1 vs. GAT 0.1 Generally, readers had no specific preference for GAD vs. GAT for global diagnostic preference, disease extent, LBD, LIM or LCE No BGD in % LCE, pre- to post-dose change in lesion-to-background ratio or no.…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 99%
See 1 more Smart Citation
“…In order for such predictions of genetics and endocrine status to be accurate, the MRI techniques must be as sensitive as possible. To enhance the contrast of MRI scans, intravenous gadolinium-based agents have routinely been administered to patients for more than 20 years and were generally considered safe ( 38 , 39 , 40 ). However, studies have indicated that gadolinium may be retained in the body, particularly in the brain when administered for pituitary imaging, so that after multiple administrations the contrast agents remained and deposits could be identified ( 40 , 41 ).…”
Section: Cranial Imagingmentioning
confidence: 99%